Event Study Testing with Cross-sectional Correlation of Abnormal Returns - Kolari, James W.; Pynnönen, Seppo (Review of Financial Studies, 2010)
This article examines the issue of cross-sectional correlation in event studies. When there is event-date clustering, we find that even relatively low cross-correlation among abnormal returns is serious in terms of over-rejecting the null hypothesis of zero average abnormal returns. We propose a new test statistic that modifies the t-statistic of Boehmer, Musumeci, and Poulsen (1991) to take into account cross-correlation and show that it performs well in competition with others, including the portfolio approach, which is less powerful than other alternatives under study. Also, our statistic is readily useable to test multiple-day cumulative abnormal returns.